2014
DOI: 10.1177/1550059414547758
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Evaluation for Early Diagnosis of Limbic Encephalitis

Abstract: Limbic encephalitis (LE) is an inflammation of structures of limbic system. It may be an autoimmune disease or secondary to a neoplasia. Onset is subacute within a few weeks and clinical presentation is characterized by behavioral changes, psychiatric symptoms, short-term memory loss, and epileptic seizures. Diagnosis is typically set after a magnetic resonance imaging (MRI) scan, revealing hyperintensity in limbic structures on T2, fluid-attenuated inversion recovery (FLAIR), and diffusion-weighted imaging (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Specific EEG features can however give clues as to the diagnosis: In HSE, in addition to background slowing, there is a temporary temporal focus showing periodic epileptiform discharges. The EEG in subacute sclerosing panencephalitis (SSPE) shows a typical generalized periodic EEG pattern repeating with intervals between 4 and 15 seconds and synchronized with myoclonus of the patient (Westmoreland, 1987;Gaspard et al, 2015;Martins and Palmini, 2015;Cag et al, 2016;Pessa et al, 2016;Saini et al, 2016). Due to the strong separation of blood and brain by the blood-brain barrier, the peripheral blood results in viral meningitis and encephalitis can be normal or only slightly abnormal and nonspecific.…”
Section: Diagnostic Featuresmentioning
confidence: 99%
“…Specific EEG features can however give clues as to the diagnosis: In HSE, in addition to background slowing, there is a temporary temporal focus showing periodic epileptiform discharges. The EEG in subacute sclerosing panencephalitis (SSPE) shows a typical generalized periodic EEG pattern repeating with intervals between 4 and 15 seconds and synchronized with myoclonus of the patient (Westmoreland, 1987;Gaspard et al, 2015;Martins and Palmini, 2015;Cag et al, 2016;Pessa et al, 2016;Saini et al, 2016). Due to the strong separation of blood and brain by the blood-brain barrier, the peripheral blood results in viral meningitis and encephalitis can be normal or only slightly abnormal and nonspecific.…”
Section: Diagnostic Featuresmentioning
confidence: 99%
“…The emergence of this phenomenon is associated with a more prolonged illness [57]. Pessa et al [104] reported a case of autoimmune-mediated LE whose EEG changes preceded the radiological changes; therefore, we should consider the diagnostic value of early EEG changes in autoimmune-mediated LE, which may be helpful for early therapy and the improvement of prognosis.…”
Section: Video Eegmentioning
confidence: 98%
“…• Electroencephalography (EEG): EEG may show signs of inflammation in the temporal lobe area, such as slow waves and epileptiform discharges. These changes, even when the MRI image is normal, allow us to suspect ALE and should prompt further diagnostics and repeat MRI in order to assess the possible progression of changes over time [33]. However, in some patients with ALE, the EEG examination may be normal [34].…”
Section: Diagnosticsmentioning
confidence: 99%